Kemampuan Spasial Siswa Tunarungu di Sekolah Luar Biasa pada Materi Bangun Ruang - Bedilius Gunur; Apolonia Hendrice Ramda (Jurnal Pendidikan Matematika RAFA, 2020)
This study aimed to describe the spatial abilities of deaf students in KM Extraordinary School in Ruteng. The population in this study were all deaf students in high school The subjects in this study were all students of class X with hearing impairment, amounting to five people. The instrument used in this study was a test item with indicators of spatial ability. To support the test results obtained, interviews were conducted directly with the students about the reasons for giving answers to each question they worked on. In addition, interviews were conducted with teachers to find out their mathematical abilities. The results showed that the spatial ability of deaf students of class X at school extraordinary KM varies according to the cognitive abilities possessed by each child. Indicators identify, classify the elements, shape, or position of a geometry object from a certain point of view are the indicators most mastered by students. As for the indicators stating the position between the elements of a building, constructing and representing geometry models still cannot be mastered by most students.